Circular economy practices and technology: a qualitative study in the fresh fruit and vegetable industry - Al-Houch, Samyra Oka (2024)
Addressing significant global food loss and waste (FLW) is crucial. With one-third of total production lost, it leads to socioeconomic and environmental consequences, including increased emissions and global hunger. The circular economy (CE) is recognized as a key solution for reducing FLW while supporting the Sustainable Development Goals (SDGs). This study aims to answer how technology enables CE practices in the fresh fruit and vegetable industry by exploring CE practices, technological effects on FLW reduction, barriers, and opportunities to the use of technologies. The selected scenario underscores the value of CE in agriculture, addressing issues of FLW. A qualitative approach is employed, utilizing semistructured interviews as the primary data collection method, complemented by the analysis of archival materials. Findings reveal that CE practices, such as useful life extension, organic waste management, and awareness initiatives, are facilitated by technology, offering benefits for producers, retailers, society, and the environment. Barriers such as cultural norms, financial constraints, and limited technical assistance prevent widespread adoption and use of technologies. The insights provided lay the foundation for future research, including quantitative assessments, comparative case studies, and sector-specific investigations, to further advance sustainability efforts within the industry. This study contributes to the achievement of the United Nations’ SDGs, particularly focusing on SDG 2, Zero Hunger, and SDG 12, Responsible Consumption and Production.